Calidad molinera de la línea promisoria de arroz L-38 (Oryza sp.) en la zona Puebloviejo, Provincia de Los Ríos - Alvarez Espinoza, Bella Elena (2025)
The main objective of this study was to determine the milling quality of the promising rice line L-38, cultivated in the Pueblo Viejo area, province of Los Ríos. Given that rice is one of the most consumed foods worldwide and a fundamental pillar of food security, it was crucial to evaluate the factors that affect the quality of this grain. During the research, various parameters related to grain quality are analyzed, such as the weight (g) of husk, percentage (%) of moisture, weight (g) of brown rice, weight (g) of white mass, weight (g) of powder, weight (g) of broken grain, weight (g) of whole grain, percentage (%) of whiteness, amylose and protein content, and the evaluation of the white center. These analyses were conducted in the Grain Laboratory of the Faculty of Agricultural Sciences at the Technical University of Babahoyo, using specialized equipment. The results obtained in the classification of whole grain rice indicated that the promising line L-38 presented a higher average weight, reaching 658.08 g, while the commercial variety SFL-11 obtained 621.38 g. Regarding the amylose content, the values were similar, with 25.73% in L-38 and 24.00% in SFL-11. Regarding the whiteness percentage, the promising line L-38 recorded an average of 40.80%, slightly higher than the 39.70% of the commercial variety. In protein, L-38 reached 9.13%, while SFL-11 obtained 8.47%, showing a minimal difference. Overall, both cultivars exhibited very similar milling characteristics with slight variations.